The impact of artificial intelligence in enhancing online learning platform effectiveness in higher education - Ahmad Hamzah, Hussin; Abu Seman, Muhamad Sadry; Ahmed, Mahfooz (Sage Publications, 2025)
Artificial Intelligence (AI) has revolutionized various sectors, and education is no exception. Online learning platforms, in particular, have benefited significantly from integrating AI technologies. AI can enhance online education's quality and effectiveness by automating tasks, personalizing learning experiences, and providing real-time feedback. This study investigates the impact of AI on online learning system effectiveness in Jordanian higher education institutions. Utilizing the DeLone and McLean IS Success Model, the research explores the relationships between AI features, system quality, information quality, service quality, user satisfaction, and platform effectiveness.